Organizational Method of EFL Undergraduate Students’ Academic Essay Writing with and Without Pre-Determined Topic - Slamet Asari; Nirwanto Maruf (Budapest International Research and Critics University, 2022)
Developing an essay writing requires a complex thought. One of this complexity is having a well-organized piece of essay writing. This study aims at investigating leaners’ writing method of organization, clinical problem in essay writing, and the difference of learners’ essay writing with and without pre-determined topic. Both qualitative and quantitative approach are employed with content analysis and statistical analysis of T-test with Paired Samples Test and Statistics. The subjects were students of semester 6 from English Education Department at University of Muhammadiyah Gresik. The findings of the study indicated that the organization of students essay writing was linearly fashioned with Cause and Effect and Comparison and Contrast method were dominantly organized. Meanwhile, students had clinical problem or difficulty covering topic that was not necessarily provided by teacher, idea development, organization, and finally the language aspect. It was also found that there were significantly different from students’ essay developed with pre-determined topic and those that were not. The findings indicate that writing an essay by leaving a topic to students will assist students to develop idea, to be able to determine appropriate method of essay organization, and to reduce possible problems they encounter during writing.